Peace Narratives as a Strategy for Digital Conflict Resolution After Indonesia’s 2024 Elections - Dewi Setyorini, Islamia; Risma Saragih, Herlina Juni; Malik, Ichsan; Setiawibawa, Rachmat; Uksan, Arifuddin (International Journal of Education, Vocational and Social Science, 2025)
This study examines the role of peaceful narratives as a conflict resolution strategy in the digital arena following Indonesia's 2024 general elections. Amidst rising political polarization, especially among youth active on social media platforms such as TikTok and X (formerly Twitter), digital spaces have become arenas for both political expression and social division. The research applies qualitative content analysis to explore how "peaceful narratives" can reduce symbolic violence and promote inclusive political awareness. Utilizing Social Identity Theory and Johan Galtung's "peace by peaceful means" framework, the study analyzes the dynamics around the viral hashtag #PrettyGirlsDon'tVote02, which symbolizes political satire and identity polarization. Findings reveal that peaceful narratives counteract digital conflicts by fostering empathy, respectful dialogue, and civic engagement, thereby strengthening social cohesion and democratic deliberation. The study recommends reinforcing political literacy, creating healthier dialogue platforms, promoting public verification of information, and encouraging positive social role models. Ultimately, peaceful narratives not only mitigate digital conflicts but also lay the foundation for national unity and resilience in Indonesia's evolving democratic landscape.